MicroRNA‐134 suppresses endometrial cancer stem cells by targeting POGLUT1 and Notch pathway proteins. Issue 2 (17th December 2014) - Gao, Yongtao; Liu, Te; Huang, Yongyi
Abstract : We aimed to ascertain the role of microRNAs (miRNAs) in regulating human endometrial cancer stem cells (HuECSCs). The expression level of miRNA‐134 (miR‐134), a member of the DLK1‐DIO3 genomic imprinted miRNA cluster, differed significantly between HuECSCs and human endometrial cancer cells (HuECCs). miR‐134 inhibited HuECSCs proliferation and migration by targeting protein O ‐glucosyltransferase 1 (POGLUT1) expression. Exogenous miR‐134 overexpression downregulated POGLUT1 and Notch pathway proteins in HuECSCs in vitro. miR‐134 overexpression affected the G2/M phase of HuECSCs and suppressed the growth of xenograft tumours formed. Thus, endogenous miR‐134 regulation in HuECSCs may suppress tumourigenesis in human endometrial carcinoma. Abstract : We isolated human endometrial cancer stem cells from endometrial cancer tissues. Low miRNA‐134 in HuECSCs correlated with POGLUT1 overexpression. We confirmed POGLUT1 mRNA to be a novel target of miRNA‐134. miR‐134 overexpression specifically inhibited HuECSCs proliferation and migration. miR‐134 overexpression suppressed Notch‐1 pathway in HuECSCs.